Tanda dan penanda simbolik orientasi sakral pada arsitektur Masjid - Muhammad Rusdi Adiputra; Purnama Salura (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
Mosques as a religious building for the Moslem Community have two orientations and they include the Qibla as the main and direction of the sky as the secondary. Praying is the main element of worship for Moslems and is recommended to be led towards the Qibla or upward direction. The mosque has been discovered not to have a sacred space but Qibla, mihrab, and Qibla marker walls are considered sacred. These sacred orientation signs and markers have been used and developed since the beginning but their existence and understanding have been eroded due to the influence of locals as well as development. Currently, the majority of the mosques in Indonesia have a centralized and strong orientation towards the upper direction when they are expected to have the main orientation in the form of Qibla direction. This study was, therefore, conducted to examine the anatomy of these mosques using semiotic theory by comparing the two mosques with several signs and markers of sacred orientation in the country. The results showed there are new signs and markers but the old ones are still significant in the mosques in the present time.